ANALISIS PENERAPAN AKUNTANSI DAN KESESUAIANNYA DENGAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (Pada UMKM di Kecamatan Sukajadi Binaan DisKop & UMKM Kota Pekanbaru) - Salmiah, Neneng; Siregar, Inova Fitri (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
Micro and SMEs are the group largest economic players in the indonesian economyand one driving the forefront of economic development .As the shaft of a revival ofthe national economy , and not the sector without problems. In addition to theproblem of capital , one of the problems faced by and as well as the weakness ofMicro and SMEs is the application of appropriate accounting SAK ETAP with havingan important role in providing information about the effectiveness and efficiency ofthe activities conducted during a period of accounting , called the financial report.This research aims to understand how the form of accounting on the application ofSMEs Sukajadi sub-district the cooperatives and Micro and SMEs Pekanbaru andwhether the application of its accounting have been in accordance with SAK ETAPwas below. The technique of analysis of data used in this research is the descriptiveanalysis , namely with the fact analysis by comparing the theory or practice ofaccounting on the implementation of cooperative sukajadi sub-district of Micro andSMEs and educated in Pekanbaru SAK ETAP alignment with and see .This analysiswill provide a thorough accounting of how the businesses run by comparing it withthe theory that there is , so can be seen whether the application of accounting atsukajadi sub-district under the jurisdiction of Micro and SMEs and cooperativepekanbaru especially in the preparation of the financial report is in accordance withSAK ETAP or not. Based on the result can only conclude that the averageaccounting for 40 % of the dept. of cooperatives, and Micro and SMEs in pekanbarusukajadi full of, or based on the steps on SAK ETAP and accounting. In other words,still accounting for 60 percent of the very simple, and it is not in accordance with TheSAK ETAP. The research which the results of 83 % of the respondents, SAK ETAPdo not understand, 70 % of respondents didn t use to make the accountingsoftware with that timely and relevant, and 70 % of respondents in the market doesnot provide additional information, and no financial information in the reportpresented, so that s incomplete. This is because the lack of knowledge,understanding as well as awareness of the importance of the application of acomplete and in accordance with accounting. etap those respondents to applyaccounting in a complete manner and in accordance in the formulation of. etapespecially financial statement is in order to obtain information on business activitiesfor one of an accounting periodKeywords : Micro and SMEs, SAK ETAP